Examines the Effect of Economic and Non-economic Factors Affecting the Environmental Performance of the Persian Gulf Countries, Spatial Panel Data - Reihaneh Ganji; Zahra Abedi; Abdolrasol Ghasemi; Amir Momamadi Nejad; Mohamad Sadegh Alipor (پژوهش‌های برنامه و توسعه)
Nowadays, environmental performance has attracted widespread attention, and it is mentioned that issues such as air pollution, global warming, habitat destruction, biodiversity threat, water scarcity crisis and desertification drastically threaten human future. The volume of oil and gas activities in the Persian Gulf countries are among the platforms that also highlight the attention to environmental performance in this area. Therefore, this article examines the effect of economic and non-economic factors affecting the environmental performance of the Persian Gulf countries. The economic factors that we selected to investigate are growth rate, degree of economic openness, energy intensity; and the non-economic factors we took into account are urbanization, democracy, population and financial development. Considering trade relations between the countries of the Persian Gulf, the spatial panel data model is used to take into account the effects of such interaction. We selected 8 Persian Gulf countries including Iran, United Arab Emirates, Bahrain, Iraq, Oman, Saudi Arabia, Qatar and Kuwait for this article. To demonstrate the relationship between economic and non-economic factors for selected countries, we chose the period 1998-2018. The findings indicate significant spatial effects related to financial development, business openness and urbanization. Findings showed significant spatial effects related to financial development, business openness and urbanization.